Gender Parity in Education: Progress, Gaps, and Policy Implications - Roopali Kudare (AG Volumes, 2024)
The existence of gender inequality has persisted throughout history. Even though there have been several attempts to promote gender equality and eradicate current gender stereotypes, it is certain that school textbooks and the course design students are required to take serve a part in maintaining gender-exclusivity. NEP 2020 is the foremost education policy of the twenty-first century and focuses on directing India's numerous developmental requirements. It is now apparent that this is a critical moment to assess the extent to which India's New Education Policy addresses gender disparities in education across all levels.